The distance-information interaction in the “Kozirev space” - Kaznacheev, Vlail; Trofimov, Alexander (Physics of Consciousness and Life, Cosmology and Astrophysics, 2009)
There are described the experiments on studying of distant field interactions between alive cages, people, plants. These supervision and experiments with "exit" from a body give the grounds for a conclusion that intellect which is considered as the information or as property, apparently, is "a special substance", the field organization of the unknown form of living matter.